Bacillus Calmette-Guérin pneumonitis after intravesical instillation: Report of two cases and a review of the literature - Spisarova, Martina; Losse, Stanislav; Jakubec, Petr; Hartmann, Igor; Kral, Milan; Ehrmann, Jiri; Szkorupa, Marek; Studentova, Hana; Melichar, Bohuslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
OBJECTIVE: Intravesical administration of bacillus Calmette-Guérin is standard adjuvant treatment of non-muscle invasive bladder cancer. In spite of the fact that this immunotherapy is locoregional, there are still risk of some complications. METHODS: We describe two cases of systemic BCG infection after intravesical administration of BCG vaccine in patients with early stage of bladder cancer. RESULTS: Both patients suffered from systemic BCG infection manifesting as BCG pneumonitis. After standard therapy with antituberculotic agents, both of them fully recovered. CONCLUSION: BCG infection can occur as a rare but potentially serious complication of this treatment procedure. Gravity of this side effect and its specific therapy require prompt and right diagnosis.
Keywords: BCG Vaccine; adjuvancia imunologická; pneumonie; Humans; BCG vakcína; Administration, Intravesical; Pneumonia; lidé; nádory močového měchýře; Adjuvants, Immunologic; Urinary Bladder Neoplasms; bacillus Calmette-Guérin; bladder cancer; intravesical therapy; aplikace intravezikální